47 Respite Care for People with Dementia and their Carers: A Qualitative Study with Multiple Stakeholders. (16th September 2019) - O'Shea, Emma; O'Shea, Eamon; Timmons, Suzanne; Irving, Kate
Abstract: Background: Traditional models of respite, particularly those based within residential care settings, may not always be effective, and there is evidence of low acceptability for some people with dementia and carers. The aim of this study was to synthesise multiple stakeholders' experiences of respite services for dementia and their perspectives on respite service development. Methods: Purposive sampling was employed. Semi-structured interviews were conducted with 35 key stakeholders, including people with dementia (n=6), carers (n=9), front-line staff (n=7), managers (n=8), policy-makers/academics (n=5). Data were interpreted inductively using thematic analysis, with a focus on latent patterns of meaning. Results: Three salient themes were identified ('Phases of Transition', 'Person-centred Respite Care'; and 'Recalibrating Respite'). Three distinct phases of respite transitions for people with dementia and carers are discussed. Respite services that actively support transitions through empathic communication regarding clients' concerns, support needs and preferences are highly valued. Clients described care resembling a 'person-centred' approach as their ideal, without using that term, but people with dementia do not always experience this type of care. The majority of providers indicated that they provide 'person-centred care', but many demonstrated a poor understanding of the concept; many of these providers have a biomedical view of dementia and the personhood status of people with dementia. Regarding service development, clients would prefer more choice, flexibility and responsiveness, including a shift away from residential provision towards an integrated continuum of personalised, strengths-focused community-based and in-home supports. Conclusion: Any recalibration of respite towards a home/community focus will require a transformation in how dementia is constructed by society, as well as a significant financial investment. Other implementation considerations include: staffing and staff competency; and the co-ordination, integration and regulation of personalised, home-based care models. Finally, it may be necessary to replace the outdated term 'respite' with an alternative nomenclature that is not discordant with person-centred care principles.